Estudo de tintas epóxis à base d’água utilizando pigmentos anticorrosivos atóxicos - Fernandes, Francisco Ivanildo Abreu (2008)
Anticorrosion performance was verified epoxy water-based inks, especially formulated for this study, pigmentary zinc chromate (CZ), zinc phosphate (FZ), phosphorus molybdate and calcium zinc (M) and silica calcium exchanger (CS). The process was conducted by exposing the samples to the natural marine atmosphere in the cabin of salt spray and total immersion in solution 10-2 mol.dm-3 NaCl. All tests for corrosion were monitored by electrochemical impedance spectroscopy and open circuit potential. adhesion test, shoaling check and visual inspection of surfaces served as complementary tests. The results suggest that the inks showed good performance in marine atmosphere and salt spray test. However, his performance was not good in total immersion tests.